Understanding traditional usage of bottle gourd (Lagenaria siceraria) peel as vegetable in comparison to pulp - SHARMA, SWATI; Singh, SK; BAHADUR, ANANT; KRISHNA, HARE; KOLE, BASUDEV; BARMAN, KALYAN; BEHERA, T K (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2021 and 2022 at ICAR-Indian Institute of Vegetable Research, Varanasi, Uttar Pradesh to evaluate bioactive compounds, antioxidant and browning enzymes activity in peel of bottle gourd (Lagenaria siceraria Stand.) fruit “Kashi Ganga” over pulp. Notably, it was observed that bottle gourd peel showed significantly higher bioactives and antioxidant capacity over fruit pulp, which is generally consumed. Two-fold stronger antioxidant capacity was observed in peel (91%) over pulp (43%). Antioxidant enzyme activities were 2.84 (catalase) and 5.67 (ascorbate peroxidase) fold higher in peel over pulp. The chlorophyll content in peel (48 µg/g FW) was 4-fold higher over pulp (12 µg/g FW). No significant difference in browning enzyme activity polyphenol oxidase and peroxidase were recorded. Higher cellulose content in peel (1.15 g/100 g FW) over pulp (0.5 g/100 g FW) was found. This indicated that health benefits can be enhanced by including peel along with pulp in diet.